Pelatihan Pembuatan Sabun Cair Bagi UMKM di Desa Lama Baru Kabupaten Langkat - Khairani Sakdiah; Halimatussakdiah; Namira Luthfiah; Sri Wahyuni (peduli riset dan pengabdian masyarakat, 2023)
students study a theory while working on its application. In doing what he wants to learn, he will automatically master the right movements or actions, so that he can master the thing he is learning perfectly. Because it includes an abstract nature of the Real Work Lecture program, a Community Training activity is needed which can facilitate the community to directly put into practice the chemistry they have learned. Making liquid soap aims to attract the interest of the community, especially UMKM in the Lama Baru Village to support UMKM activities in the village. This activity is carried out through stages, namely the first stage is the introduction, the second stage is the socialization stage, the third stage is the manufacture of liquid washing soap and the final evaluation stage. The target to be achieved in this community service is, in practice the community is able to make liquid hand washing soap, and can make it a source of income. Based on observations during this community service activity, positive results were obtained, namely participants showed good attention to the material and were able to apply liquid washing soap well.